A Model For Leaching Of Glauconitic Sandstone Using Reduced Time Plot Concept - L. S. Rao; B. R. Rao; B. Govindarajan; T. C. Rao (Society for Mining, Metallurgy & Exploration, 1994)
Laboratory leaching experiments were conducted to extract potassium from glauconitic sandstone, and the effects of important variables were studied. The reduced time plot (RTP) for all of the variables obtained from the experimental data has been quantified by this simple equation: R = 100 (1 - exp (-0.693 *(T/T50)0.605) The time required for 50% extraction (T50) has been correlated by a regression equation to variables such as acid strength, temperature, fluorite: glauconite ratio and % solids. Both of these equations were used to predict the extraction percentage at different process-variable levels. In addition, several other experiments were conducted at arbitrary levels of the variables to verify the equations developed.